Prodromal headache in MOG-antibody positive optic neuritis - Asseyer, Susanna; Hamblin, Josh; Messina, Silvia; Mariano, Romina; Siebert, Nadja; Everett, Rosie; Kuker, Wilhelm; Bellmann-Strobl, Judith; Ruprecht, Klemens; Jarius, Sven; Leite, Maria Isabel; Brandt, Alexander U.; et al. (Multiple Sclerosis and Related Disorders, 2020)
Background: Myelin oligodendrocyte glycoprotein antibody (MOG-Ab) disease is an inflammatory autoimmune condition of the central nervous system, defined by antibodies (Abs) against MOG. Of the various clinical phenotypes optic neuritis (ON) is the commonest. We have observed that some patients with MOG-Ab ON present with a severe associated headache. Objective: To highlight the importance of headache in MOG-Ab related optic neuritis. Methods: Clinical and MRI data from MOG-Ab patients with ON (n = 129) were obtained from observational cohort studies and clinical notes at the NeuroCure Clinical Research Center, Charite Berlin and at the Diagnostic and Advisory Service for Neuromyelitis Optica, John Radcliffe Hospital, Oxford. Results: Sixty-four of 129 MOG-Ab patients (49.6%) reported >= 1 headache-related ON. Headache usually started a few days prior to visual loss and extended from the ocular region to the periorbital and fronto-temporal area, sometimes mimicking migraine. Of those, thirty-two patients (50%) reported severe headache. Two patients did not have headache. No headache history was recorded for 63 patients. MRIs performed acutely during headache-related MOG-Ab ON (n = 15) showed anterior ON with extensive swelling and edema of the optic nerve/s in all patients, either unilaterally (n = 5) or bilaterally (n = 10). Peri-optic cerebro-spinal fluid (CSF) was undetectable due to the inflammatory extension in 12 out of 15 patients. Conclusion: Our findings indicate that acute MOG-Ab ON shows florid intra-orbital and peri-optic inflammation, likely to involve meninges and nociceptive fibers around the optic nerve. This may explain the frequent and often severe headache that precedes the visual deficit, sometimes misdiagnosed as migraine.
Gesehen am 13.07.2020